FEATURES OF ISLET-LIKE CLUSTERS GENERATION IN PANCREATIC DUCTAL CELL MOLOLAYER CULTURING - L. A. Kirsanova; G. N. Bubentsova; N. V. Baranova; N. N. Skaletskiy; V. A. Zaydenov; I. A. Pushkova (Вестник трансплантологии и искусственных органов)
Newborn rabbit pancreatic cell monolayer was obtained as we described earlier.The cultivated epithelial cells were shown by immunofluorescence to express special ductal marker CK19 and were insulin-and glucagon- negative for 10–15 days. A few fusiforms of nestin-positive cells were found in monolayer. Over 2 weeks in serum-free medium the plaques of epithelial cells became crowded and formed 3-dimentional structures – islet- like clusters. Islet-like clusters contain some insulin- and glucagon-positive cells recognized by immunohysto- chemistry staining. Pancreatic endocrine cell generation in 3-dimentional structures is discussed.